Effects of concurrent in-season training on physiological functions required for top handball performance athletes - Belkadi, A.; Beboucha, W.; Benhammou, S.; Moussa, M.; Bouzoualegh, M.; Dairi, A. (Scientific Journal of Sport and Performance, 2025)
This study examined the physiological effects of combining contrast complex training (CCT) with either repeated short sprints (RSE) or high-intensity intervals (HIIT) on elite male handball players during the competitive season. The goal was to identify which training method more effectively enhances strength, endurance, and sprint performance. Fifteen elite handball players were divided into two groups during a 12-week training program, conducted alongside their regular handball practice. The RSE group (n = 8) performed 10 shuttle sprints (2x15m) with passive rest, while the HIIT group (n = 7) completed 5 repetitions of 30-second all-out sprints with directional changes. Both groups participated in CCT exercises, including squats at 90% of 1RM, jump squats at 50% of body weight, and drop jumps from 30 cm. Performance was assessed before and after the intervention using tests for jump squat rate of force development (RFD), 5-jump distance, 30m sprint, repeated shuttle sprint ability (RSSA), maximal squat strength, Yo-Yo intermittent recovery (YYIRT 1), and VO2max. Both groups significantly increased maximal squat strength, with the RSE group improving by 8.8% and the HIIT group by 7.4% (p < .01). The HIIT group showed a greater improvement in RFD (63.3% vs. 56.3%, p < .05). VO2max increased by about 2% in both groups. YYIRT 1 improved by 9.4% in the RSE group and 5.8% in the HIIT group. However, acceleration (5m sprint) declined in both groups, more notably in the RSE group (-5.7%). RSSA performance deteriorated in the RSE group, while the HIIT group significantly enhanced their fatigue resistance, with a 39.1% improvement in Sdec at RSA (p < .09). CCT increased strength and RFD but did not improve acceleration. HIIT was superior to RSE in maintaining or improving repeated sprint ability, making it the preferred method for elite handball players during the competitive season.